2021
DOI: 10.1101/2021.05.25.445564
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The RIFF: an automated environment for studying the neural basis of auditory-guided complex behavior

Abstract: Behavior consists of the interaction between an organism and its environment, and is controlled by the brain. However, while brain activity varies at fast, sub-seconds time scales, behavioral measures tend to be temporally coarse, often limited just to the success or failure in a trial. The large gap between the temporal resolutions at which brain and behavior are observed likely impedes our understanding of the neural mechanisms underlying behavior. To overcome this problem, we developed the RIFF: an interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Several studies using animal models, including nonhuman primates, have also identified an auditory field in the posterior insula (Linke & Schwegler, 2000;Remedios et al, 2009;Rodgers et al, 2008). While this insular auditory field does receive input from primary and secondary auditory areas, it also receives direct parallel input from the auditory thalamus, evidenced in part by pure-tone responses in the insular auditory field sometimes having a lower response latency than the primary auditory cortex (Jankowski et al, 2023;Sawatari et al, 2011;Takemoto et al, 2014). Our own results parallel animal models, as we observed faster (or equivalently fast) responses to auditory playback stimuli in the posterior insula compared to primary (HG, PT) and higher order (STG, STS) auditory areas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using animal models, including nonhuman primates, have also identified an auditory field in the posterior insula (Linke & Schwegler, 2000;Remedios et al, 2009;Rodgers et al, 2008). While this insular auditory field does receive input from primary and secondary auditory areas, it also receives direct parallel input from the auditory thalamus, evidenced in part by pure-tone responses in the insular auditory field sometimes having a lower response latency than the primary auditory cortex (Jankowski et al, 2023;Sawatari et al, 2011;Takemoto et al, 2014). Our own results parallel animal models, as we observed faster (or equivalently fast) responses to auditory playback stimuli in the posterior insula compared to primary (HG, PT) and higher order (STG, STS) auditory areas.…”
Section: Discussionmentioning
confidence: 99%